Cumulative benefits from trade liberalization for the South African economy - Matthias Bauer; Andreas Freytag (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
South Africas trade barriers are still relatively high compared to other emerging market economies, and its industrial policy still preferentially treats certain industries. Based on a static GTAP model, we estimate the economic impact of further trade liberalization on the South African economy. We particularly take into account core NTBs on tradable commodities and the costs imposed by cross-border trade facilitation, which is particularly inefficient in South Africa. Our results indicate that a full liberalization package, including a reduction of core NTBs as well as a substantial increase in the efficiency of cross-border trade facilitation to the levels of Singapore, would cause the South African GDP to rise by up to 4.51 per cent. This implies an increase in aggregate welfare of up to 21 billion US Dollars. This sum is the equivalent of what should be given to the South African economy in order to leave citizens as well of as after the implementation of a full liberalization package, given South African policy-makers abstain from further trade liberalization policies.
Keywords: D58; K2; L5; F1; F17; 330; GTAP; international trade; non-tariff trade barriers; South Africa; trade policy